RELASI KUASA ANTARA PONDOK PESANTREN DAN PARTAI POLITIK (STUDI KASUS PONDOK BUNTET PESANTREN DAN PARTAI KEBANGKITAN BANGSA PADA PEMILU LEGISLATIF DPRD KABUPATEN CIREBON 2019) - Mohammad Iqbal Azad (2023)
This study aims to find out how the patron-client relationship is between Pondok Buntet Islamic Boarding Schools and the Awakening Party in the 2019 Cirebon Regency DPRD Legislative Election. This research case study focuses on the patron-client relationship of the National Awakening Party (PKB) and Pondok Buntet Islamic Boarding Schools. The existence of a pattern of patron-client relations between political parties and Islamic boarding schools encourages the emergence of benefits between the two parties. The patron-client relationship is based on an unequal relationship, because it reflects differences in status. Political parties as one of the elements of democracy in Indonesia certainly need a mass base as the strength of the party. The relationship between PKB's patron client and Pondok Buntet Islamic Boarding School is related to the needs of the mass base. This study uses a qualitative descriptive method, namely by relying on primary data and secondary data. The theory used in this research is Jemes C. Scott's theory regarding Patron-Client as a research analysis tool. The results of this study indicate that the patron-client theory is able to explain exchange relationships involving patrons (Pondok Buntet Islamic Boarding Schools) who have a higher social status so that they are able to use their influence and resources to provide benefits for clients (PKB), namely in the form of a voice bassist so that PKB was able to achieve the largest number of DPRD seats in the Cirebon Regency DPRD legislative elections in 2019.